A new species of the thorid genus Paralebbeus Bruce & Chace, 1986 (Crustacea: Decapoda: Caridea) from the deep sea of the Northwestern Pacific Ocean - Xu, Peng; Liu, Feng; Ding, Zhongjun; Wang, Chunsheng (Zootaxa, 2016)
During recent dives by the Chinese manned submersible “Jiaolong”, some shrimp specimens were sampled from the deep sea of the Northwestern Pacific Ocean. A new species of the caridean family Thoridae, Paralebbeus jiaolongi sp. nov., is described and illustrated in this study. The rostrum armed with only one subterminal ventral tooth can easily distinguish the new species from its congeners.